Breakthrough kaizen events (Manufacturing insights)
This video describes an actual kaizen event at Lantech Corporation in Louisville, Ky. Kaizen means "good change" in Japanese. The goals of kaizen are to solve problems and eliminate waste. Lantech was able to improve productivity by 12%, eliminate quality problems, and solve several safety and ergonomic issues.